ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PT TIRTA MAHAKAM RESOURCES Tbk TAHUN 2017- 2021 - Siwi Nur Indriyani (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
The purpose of this study is to determine and analyze bankruptcy prediction at PT. Tirta Mahakam Resources Tbk for the 2017-2021 period. This type of research is included in the category of quantitative descriptive research. The research data source is the company's annual financial report data for the period 2017 - 2021 which has been audited and can be accessed via the website www.idx.co.id. The sampling technique used is porposive sampling technique. The analysis technique used in this study is the Altman ZScore model using ratios (Net Working Capital to Total Assets, Earnings Before Tax to Total Assets, Retained Earnings to Total Assets, Sales to Total Assets, and Total Equity to Total Assets). The results of the analysis show that the model can adapt to the environment and economic conditions in Indonesia as an early warning system to mitigate future bankruptcy risks, so that management can immediately take preventive action.